Symplectic Difference Schemes for Hamiltonian Systems in General Symplectic Structure (Journal of Computational Mathematics, 1991)
We consider the construction of phase flow generating functions and symplectic difference schemes for Hamiltonian systems in general symplectic structure with variable coefficients.